The Influence of Difference Exercise Anaerobic Interval Methods Against The Results of The Shooting Ratio of Underbasket Height and Long Limbs - Satria, Agni Herarta Anindya (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2017)
The purpose of this research is to know (1) the difference between the influence of the ratio of anaerobic interval exercise 1:3 exercise, anaerobic interval and the ratio of 1:5 against shooting underbasket results, (2) the difference between the ratio shooting results underbasket height: long legs and high ratio of height: long limbs are low, (3) the influence of the interaction between exercise anaerobic interval ratio and the ratio of height: the length of the limbs results shooting underbasket. This research uses experimental methods with a 2 x 2 factorial design. Based on the results of the analysis of the data shows that: (1) there is a significant influence on the differences between the ratio of anaerobic interval exercise 1:3 exercise anaerobic interval and the ratio of 1:5 against results shooting underbasket, pvalue < 0, 05. Influence of exercise anaerobic interval with the ratio of 1:5 has better results than an anaerobic interval workout with a 1:3 ratio with average results respectively 9 and 8, 43, 43. (2) no difference shooting results significant underbasket between height ratio: the ratio of height and limb length height: long limbs, pvalue < 0.05. Results of shooting underbasket earned by the sample with a ratio of height: the length of the limb with a low category better than the sample with a ratio of height: long limbs with high category with average results each 19.14 and 16.67. (3) there is the influence of the interaction between exercise anaerobic interval ratio and the ratio of height: the length of the limbs results shooting underbasket, pvalue < 0, 10.